Warning Against Greed in Proverbs 21:25-26 and Failing Ponzi Schemes in Nigeria - Uroko, Favour Chukwuemeka (Sekolah Tinggi Teologi Injili Indonesia Samarinda, 2025)
This study explores the warning against greed in Proverbs 21:25–26 and examines its relevance to the rise and collapse of Ponzi schemes in Nigeria. The aim is to draw moral, financial, and social lessons from the biblical text and apply them to modern-day economic behavior, with the goal of promoting ethical financial practices and protecting vulnerable individuals from fraud. Nigeria has witnessed a surge in Ponzi schemes, such as MMM, Ultimate Cycler, and others, which have led to widespread financial losses. Many individuals, driven by greed and the desire for quick wealth, ignore warnings and invest in fraudulent schemes. This issue reflects a deeper moral and societal challenge rooted in the pursuit of unearned riches, as warned against in Proverbs 21:25–26. There is a need to address both the spiritual and socio-economic factors fueling this trend. The research adopts a qualitative and interpretive approach, combining biblical exegesis of Proverbs 21:25–26 with a case study analysis of major Ponzi schemes in Nigeria. Data was collected from secondary sources including academic journals, financial reports, news articles, and religious literature. The study also applies ethical and theological frameworks to understand the influence of greed on financial decision-making. The study finds that Proverbs 21:25–26 offers a timeless warning against laziness and the craving for quick gain, both of which are prominent motivations behind participation in Ponzi schemes. The findings reveal that financial greed, combined with low financial literacy and economic desperation, makes individuals more susceptible to fraudulent investment opportunities. The study also highlights the failure of regulatory agencies and the lack of faith-based financial education as contributing factors.